2015
DOI: 10.1002/jez.1965
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise affects embryo mortality and nestling growth rates in captive zebra finches

Abstract: Over the past two decades, studies of songbird populations have detected decreases in the reproductive success of individuals living in urban areas. Anthropogenic noise is considered to be particularly detrimental, however the exact relationship between noise and reproductive success is still unclear because noise is often correlated with many other detrimental factors (e.g., predation, reduced territory quality). We used an experiment to specifically test the effects of urban noise on reproduction of captive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 56 publications
(69 reference statements)
5
75
1
Order By: Relevance
“…Without being able to pinpoint down the lowest threshold of negative impact yet, the combined evidence from our and other studies suggests that for sound levels from 70 dB(A) and higher (<15 m to the highway), traffic noise may affect communication, foraging, physiology and reproduction (Cynx et al, 1998;Potvin & MacDougall-Shackleton, 2015;Potvin et al, 2016;Villain et al, 2016;Dorado-Correa et al, 2018). Wild birds of other species that were chronically exposed to anthropogenic noise were found to have altered glucocorticoid levels (Kleist et al, 2018; but see Crino et al, 2013), which in turn will raise energy demands (Jimeno et al, 2018).…”
Section: Recording Distance Dependent Response Patternmentioning
confidence: 77%
See 2 more Smart Citations
“…Without being able to pinpoint down the lowest threshold of negative impact yet, the combined evidence from our and other studies suggests that for sound levels from 70 dB(A) and higher (<15 m to the highway), traffic noise may affect communication, foraging, physiology and reproduction (Cynx et al, 1998;Potvin & MacDougall-Shackleton, 2015;Potvin et al, 2016;Villain et al, 2016;Dorado-Correa et al, 2018). Wild birds of other species that were chronically exposed to anthropogenic noise were found to have altered glucocorticoid levels (Kleist et al, 2018; but see Crino et al, 2013), which in turn will raise energy demands (Jimeno et al, 2018).…”
Section: Recording Distance Dependent Response Patternmentioning
confidence: 77%
“…In the experiment, the tested birds avoided noisy conditions to move into a quieter space. This behaviour would confer an advantage outside the laboratory as complementary research in zebra finches has already shown that noise negatively impacts zebra finches: it increases vigilance reducing food uptake during foraging (Evans et al, 2018), affects intra-pair communication (Villain et al, 2016), offspring initial growth rates (Potvin & MacDougall-Shackleton, 2015), reduces telomere length (Dorado-Correa et al, 2018) and affects song learning (Funabiki & Funabiki, 2009;Potvin et al, 2016).…”
Section: Noise Avoidance In the Laboratory And In The Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study carried out in laboratory conditions reported no impact of urban noise on reproductive output in the zebra finch Taeniopygia guttata . However, females in the noisy condition made more nesting attempts and laid more eggs but had a lower hatching success due to higher embryo mortality (Potvin & MacDougall‐Shackleton, ). In the domestic sparrow Passer domesticus, one study failed to find a noise impact either on the clutch size or on the number of fledglings (Meillère, Brischoux, & Angelier, ) while a different one has shown experimentally that urban noise had a negative impact on the condition of nestlings and the number of fledged young (Schroeder, Nakagawa, Cleasby, & Burke, ).…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study carried out in laboratory conditions reported no impact of urban noise on reproductive output in the zebra finch Taeniopygia guttata. However, females in the noisy condition made more nesting attempts and laid more eggs but had a lower hatching success due to higher embryo mortality (Potvin & MacDougall-Shackleton, 2015). In the domestic sparrow…”
Section: Noise Impact On Clutch Sizementioning
confidence: 99%